High order approximation to new generalized Caputo fractional derivatives and its applications - Li, Xuhao (2018)
In this paper, we shall develop a generalized L1 − 2 formula for new generalized fractional Caputo derivatives. It is theoretically shown that this new approximation achieves O(τ3−α) (τ is the step size) which improves earlier work done to date. Also, numerical tests and an application are presented to demonstrate the efficiency and accuracy of the proposed method.